The importance of preexisting drug resistance due to overexpression of P-glycoprotein for the formation of resistance to bortezomib - L. A. Laletina; N. I. Moiseeva; A. F. Karamysheva (Успехи молекулярной онкологии, 2020)
Objective of the study. In our work we investigated the effect of pre-existing drug resistance by the mechanism of activation of ABC transporters – P-glycoprotein (Pgp) overexpression – on the development of resistance to the proteasome inhibitor bortezomib.Materials and methods. Cultures RPMI8226 and K562 / i-S9 (with Pgp overexpression) and their bortezomib-resistant sublines RPMI8226 / btz-6 and K562 / i-S9vlc were used as models. The methods used were MTT test, flow cytometry, Western blot and real-time polymerase chain reaction using the Human Signal Transduction Pathway Finder system.Results. The expression of the main PI3K-AKT and NF-κB signaling pathways did not change in RPMI8226 / btz-6 subline cells. However, AKT kinase expression was significantly increased and PTEN protein expression was reduced in K562 / i-S9vlc cells with Pgp-overexpression. Significant changes in gene expression (42 %) were found in RPMI8226 / btz-6 cells related to a number of main signaling pathways in the tumor cell, namely: activation of 3–4 genes in signaling pathways related to hypoxia, oxidative stress, PPAR and p53. The highest activation in these cells was found in the TGFβ signaling pathway. In resistant K562 / i-S9vlc cells, expression of only 5 genes (10 %) increased: Fas, HMOX1, CPT2, ICAM, and SOCS3. Three genes were also identified that changed in both resistant sublines: Fas, HMOX1 and CPT2. Further, we showed that in the RPMI8226 / btz-6 subline, along with changes in the expression of signal transduction genes, there is a large pool of CD138-negative cells, and in the K562 / i-S9vlc subline, the number of cells expressing CD34 increases and the number of CD13 decreases.Conclusion. We found that different signaling pathways are involved in the formation of resistance to bortezomib in the absence of Pgp expression and its overexpression. In addition, a cell line without activated resistance pathways requires more extensive rearrangements in the signal system to acquire resistance to bortezomib. However, in both cases, bortezomib leads to a change in the immunophenotype of the cells – to the appearance of dedifferentiated subpopulations.